EDUCATIONAL MEDIA JIGSAW PUZZLE GAMES AS AN EFFORT TO INCREASE DENTAL AND ORAL HEALTH KNOWLEDGE FOR GRADE I STUDENTS MI MIFTAHUL FALAH SINANGGUL IN THE WORKING AREA OF THE MLONGGO HEALTH CENTER, JEPARA REGENCY - Anugrah Nurul Ramadani Rabbi; Anita Pujianti; Amalia Putri Fadilla; Sri Nurul Amaliah; Tri Suprapti; Aji Saipul Rakhman; Sukini Sukini; Lanny Sunarjo (Wealth Community Empowerment, 2025)
Elementary school age children are classified as a group that is prone to dental and oral diseases, this is because in elementary school age children behavior in caring for dental and oral health is still lacking. The results of Basic Health Research (Riskesdas) in 2018 showed that 54.0% of dental and oral health problems were 5-9 years old in school. The dental and oral health of school-age children needs serious attention from health workers, both from dentists and dental and oral therapists. The most common disease suffered by elementary school-age children is caries. The main cause of caries is due to the continuous accumulation of plaque that is not cleaned. Dental health education needs to be instilled from an early age in children so that they know the right way to maintain the health and hygiene of their teeth and mouth. Efforts to prevent the occurrence of dental and oral diseases in elementary school children are by conducting a dental and oral health education program for students. The goal is to increase students' knowledge in maintaining and maintaining dental health. The methods used in this service are the method of playing, lecturing, and demonstrating to the respondents. Based on the results of the activities that have been carried out in the service, the respondents gave a positive response and there was an increase in knowledge and dental and oral hygiene.